Analysis of the Influence of Corporate Social Responsibility, Profitability, Leverage and Activity on Energy Sector Company Value - Mohamad Katami Aji Saputra; Sumilir Sumilir; Yudi Nur Supriadi (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
This study aims to determine the effect of Corporate Social Responsibility proxied with CSR funds, Profitability proxied with Return On Asset (ROA), Leverage proxied by Debt to equity Ratio (DER) and Activity proxied by Inventory Turnover (ITO) toward Firm Value proxied by Price to Book Value (PBV). Population in this study are energy companies listed on Indonesia Stock Exchange (IDX) 2017-2021. The technique of determination of the sample using the method of purposive sampling and obtained 37 sector energy companies with a research period of five years. Hypothesis testing in this research using Data Panel Regression Analysis with E-Views 12.0 program and significance level of 5%. The result of the research shows that (1) corporate social responsibility (CSR funds) no significant effect on firm value (PBV), (2) profitability (ROA) has a significant positive effect on firm value (PBV), (3) Leverage (DER) has significant positive effect on firm value (PBV), (4) activity (ITO) no significant effect on firm value (PBV). Keywords: corporate social responsibility, profitability, leverage, activity and firm value